In vitro antibiotic susceptibility patterns of bacterial keratitis isolates in Oxford, UK: a 10-year review - Orlans, H; Hornby, S; Bowler, I (Nature Publishing Group, 2011)
Purpose To analyse the spectrum of bacterial keratitis isolates and their in vitroantibiotic susceptibilities over a 10-year period in Oxford, UK; and to compare the in vitroefficacy of ciprofloxacin with that of the combination of gentamicin and cefuroxime over the same period. Methods All culture-positive corneal scrapes received from the Oxford Eye Hospital between July 1999 and June 2009 were identified retrospectively using a local microbiology database. For analysis of trends over time, the data was split into two equal 5-year periods. Statistical analysis was done using the χ 2 and Fisher exact tests. Results Over the 10-year study period, 467 corneal scrapes were performed of which 252 (54.0%) had positive bacterial cultures, growing a total of 267 organisms. The most commonly isolated bacteria were Staphylococci(40.1%) followed by Pseudomonasspecies (28.5%), other Gram-negative species (17.2%), Streptococci(7.1%), and Corynebacteria(6.0%). Between the first and second time periods there was an increase in the number of coagulase-negative Staphylococciand an increased resistance of the non-Pseudomonas Gram-negative group to chloramphenicol. Of the 189 isolates tested for sensitivity to both empirical antibiotic regimens, 176 (93.2%) were susceptible to ciprofloxacin whereas 188 (99.5%) were susceptible to either gentamicin or cefuroxime (P=0.0015). Conclusions The spectrum of bacterial keratitis isolates and their in vitroantibiotic sensitivity patterns have generally remained stable over time. The combination of gentamicin and cefuroxime provides a broader spectrum of antimicrobial cover than ciprofloxacin monotherapy in Oxford, although both regimens continue to be appropriate choices for the initial management of this condition.